Kvalita Služeb v dopravním podniku Jihotrans - Stuchlý, Jaroslav; Šolc, Ladislav (Univerzita Pardubice, 2016)
Customers of transport company Jihotrans values in the survey five basic factors for the quality of its services. In total, these evaluations define a variable overall quality of services. In the article is first performed a descriptive analysis of this variable. Using basic statistical methods, the significant dependence of the overall quality of services provided by some other qualitative and quantitative variables included in the questionnaire was then explored. In addition to analysis of variance there were used models of correlation and regression analysis, including models with dummy variables. Using analysis of variance, it was shown that the overall quality of service depends considerably on the competitive advantages of the company. It was also derived linear regression model dependence of this variable on the evaluation of the development of enterprise competitiveness. As the best model, was derived regression model which expresses the dependence of overall service quality on a pair of variables assessment of the development of enterprise competitiveness and competitive advantage for enterprises. This model was described computationally and also was presented graphically.
Quality of Services in Transport Company Jihotrans
Keywords: Transport Company; Quality of services; Data analyses; Competitiveness; Advantages of the company against the competition; Descriptive and inductive statistics; Correlation and regression analysis; C1; M3; N7